Stephen Dixon's Novels: Autobiographicality as Transgression - Honcharova, Yuliia; Lipina, Victoriia (Respectus Philologicus, 2021)
The idea advanced in the paper is to theorize the mechanisms of autobiographicality in Stephen Dixon’s novels that are viewed as a radical renewal of autobiographical narrative, where the modality of disappearance/return of the subject produces a new mode of life-writing. We propose the term “autobiographical transgression” to capture the essence of this renewal started by three representative figures – John Barth, Stephen Dixon, and Joseph Heller that can be reduced neither to autobiography as a genre, nor to “transgressive autobiography” as its generic variant. Dixon finds a new form for representing autos. He creates the character with the name-deixis I. that personifies a fiduciary subject, thus, suggesting a provocative restatement of postmodernist generic problems. In the novels I. and End of I. the autobiographical hero I. exists simultaneously as a metaphor of the author’s presence in the text, as the subjective author’s I and as a character in the novel − an objectified, semi-functional, distancing I. The transplanting of life experience manifests itself in a special kind of repersonalization and double coding of the traditional autobiographical subject.
Keywords: autobiographical trangression; Stephen Dixon; I.-texts; auto/bio/graphicality; a fiduciary subject